An Investigation of Different Offshore Wind Turbine Jacket Support Foundation Models Designed for Central Mediterranean Deep Waters. Issue 3 (June 2013) - Gauci, Thomas; Sant, Tonio; Muscat, Martin; Mollicone, Pierluigi; Camillieri, Duncan
The trend for improving the cost effectiveness of offshore wind turbines is to maximise wind turbine size while minimising support structure costs. Minimising the support structure costs in deeper waters is undoubtedly more challenging. Studies have shown that the type of foundation model used at the base of the support structure has a significant influence on the overall design result. Two foundation models are studied independently: the pinned foundation and the rigid foundation. The effect of the foundation type on the modeled overall support structure characteristics, are investigated. The objective of this study is to produce an optimised jacket design for a 70 metre water depth in the central Mediterranean region. The study shows that different foundation types influence the internal loads of the individual jacket members and consequently affect the structure's natural frequencies. The final result shows that the jacket structure with a rigid foundation design was 5.4 tonnes lighter than its pinned counterpart.